Research and Manufacturing of Non-circular Gear Vibration Characteristic - Huoying Zhao (Jixie chuandong)
Aiming at the problem of noise and vibration in the operation of gear mechanism， the vibration reduction characteristics of non-circular gear are studied. The influence of the deviation between the gear center and the center of the circle on the kinematics and oscillation characteristics is analyzed. The results show that a larger deviation will result in a smaller resonance amplitude due to the change in mesh frequency， and at the same time will lead to a higher additional dynamic load on the mechanism. The shape of the gear center is determined，which provides relatively small resonance amplitudes and minimal additional dynamic loads. A mechanical device that can cut slightly non-circular gears on a hobbing machine without numerical control machine is developed.